Influence of surface modifications on the degradation of standard-sized magnesium plates and healing of mandibular osteotomies in miniature pigs. Issue 2 (February 2020) - Naujokat, H.; Ruff, C.B.; Klüter, T.; Seitz, J.-M.; Açil, Y.; Wiltfang, J.
Abstract: Biodegradable magnesium alloys are suitable osteosynthesis materials. Despite the alloy composition, surface modifications appear to have an influence on the degradation process and biocompatibility. The aim of this study was to investigate the impact of hydrogenation and fluoridation of the surface in a mandibular osteotomy model. Standard-sized plates and screws were implanted in an osteotomy at the mandibular angle in nine miniature pigs. The plates and screws were harvested together with the adjacent tissues at 8 weeks after surgery and were investigated by micro-computed tomography and histological analysis. The bone healing of the osteotomy was undisturbed, independent of the surface properties. The adjacent bone tissue showed new bone formation at the implant surface; however, formation of some lacunae could be observed. The corrosion was between 9.8% and 11.6% (fluoridated < hydrogenated < non-modified) in histological specimens, while radiologically neither the volume nor the density of the osteosynthesis material was reduced in any treatment group. The soft tissues exhibited full biocompatibility with every surface property. In summary, surface modification by hydrogenation and fluoridation did not significantly influence bone healing, biocompatibility, or corrosion kinetics of the magnesium osteosynthesis at the mandibular angle.